RELATIONSHIP OF KNOWLEDGE WITH DRUG COMPLIANCE IN TUBERCULOSIS (pulmonary TB) PATIENTS IN RSUD DR. R. SOEDJONO SELONG - Yogi Mujizat (Scientia Integritas Utama, 2022)
Abstract: The coverage of finding positive smear pulmonary tuberculosis cases in the province of NTB, Lombok island, is the highest and every year it increases in East Lombok Regency, namely 17%. Knowledge and adherence to taking medication is one of the factors that determine the success factor in the treatment of pulmonary tuberculosis. The type of research used in this research is descriptive non-experimental with a cross-sectional research design. This study was used to determine the relationship between knowledge and adherence to medication in tuberculosis (pulmonary TB) patients who were on outpatient treatment at RSUD Dr. R. Soedjono Selong, East Lombok Regency. Tuberculosis patients in RSUD Dr. R. Soedjono Selong who met the criteria and were willing to be respondents amounted to 78 people.For data collection, the independent variable is the knowledge of patients with pulmonary TB disease and the dependent variable is adherence to taking OAT. Using the instrument in the form of a questionnaire developed by the researcher himself, while the data analysis technique used the Chi-Square statistical test. The results showed that 84.6% of pulmonary TB patients had good knowledge of TB disease. 89.7% compliance rate in taking OAT was compliant. The Chi Square test of the two variables obtained a calculated X2 value 56,27 which means that there is a relationship between the patient's level of knowledge and adherence to taking OAT at Dr. Hospital. R. Soedjono Selong.